Apnea (Revista de Ensino em Artes, Moda e Design, 2024)
The photo-performance series "Apneia" (2019 - in process) continues to record changes in the landscape due to permanent human interference, with images of a vast and impressive burnt landscape in a transition zone to the Cerrado, ironically taken on August 9, 2019, one day before what would be baptized as "Day of Fire", an apparently coordinated action that would result in one of the biggest environmental scandals on a global scale.
Keywords: unsustainability; dystopia; environmental crime; body; photoperformance